OP23 Efficacy and safety of vedolizumab SC in patients with moderately to severely active Crohn's disease: Results of the VISIBLE 2 study. (15th January 2020) - Vermeire, S; Sandborn, W; Baert, F; Danese, S; Kobayashi, T; Loftus, E V; Bhatia, S; Kisfalvi, K; Rosario, M; Zhang, W; D'Haens, G
Abstract: Background: Vedolizumab (VDZ) is a gut-selective, humanised, monoclonal α 4 β 7 integrin antibody for the treatment of patients with moderately to severely active ulcerative colitis (UC) or Crohn's disease (CD). VDZ is currently an intravenous (IV) therapy; a subcutaneous (SC) formulation is under development to provide patients with an alternative route of administration for maintenance treatment for UC and CD. Here we present the first data from the phase 3 study of VDZ SC maintenance treatment in CD. Methods: VISIBLE 2 (NCT02611817; EudraCT 2015-000481-58) was a randomised, double-blind, placebo (PBO)-controlled phase 3 trial of VDZ SC as maintenance treatment in adults with moderately to severely active CD. Patients ( n = 644) received open-label VDZ 300mg IV induction therapy at Weeks 0 and 2. At Week 6, clinical responders (defined as patients with a ≥70-point decrease in CD Activity Index [CDAI] from baseline) were randomly assigned to receive vedolizumab SC (108 mg every 2 weeks [Q2W]), or placebo (Q2W) for up to 52 weeks. The primary endpoint was clinical remission at Week 52 (defined as CDAI score ≤150). Rank-ordered secondary endpoints were enhanced clinical response at Week 52 (a drop of ≥100 in CDAI score), corticosteroid (CS)-free clinical remission at Week 52, and clinical remission at Week 52 in anti-tumour necrosis factor (TNF)-naïve patients. Finally, VDZ immunogenicity and predefined adverse events of special interest were assessed. Results: Patients who responded to VDZ IV induction at Week 6 ( n = 409) were randomised to VDZ SC ( n = 275) or PBO ( n = 134) maintenance and received at least 1 dose of study drug; 61% and 53%, respectively, were previously exposed to anti-TNF therapy. At Week 52, 48.0% of patients on VDZ SC vs. 34.3% on PBO were in clinical remission ( p = 0.008, Figure). Enhanced clinical response at Week 52 was reached by 52.0% vs. 44.8% of patients on VDZ SC vs. PBO, respectively ( p = 0.167). Among patients on concomitant CS at baseline (VDZ SC, n = 95; PBO, n = 44), 45.3% receiving VDZ SC vs. 18.2% receiving PBO achieved CS-free clinical remission at Week 52. Of anti-TNF-naïve patients (VDZ SC, n = 107; PBO, n = 63), 48.6% vs. 42.9% were in clinical remission at Week 52 in the VDZ SC and PBO arms, respectively. Injection-site reactions were reported for <3% of patients treated with VDZ SC. Serious infections, malignancy, and liver injury were ≤5% for both arms. Anti-VDZ antibodies were detected in 7 (2.5%) patients treated with VDZ SC arm; 4 of 7 patients developed neutralising antibodies. No new safety signals were observed. Conclusion: Among VDZ IV induction responders, significantly more patients on maintenance VDZ SC than PBO achieved clinical remission at Week 52. The safety findings with VDZ SC remain in line with the known safety profile of VDZ IV in patients with CD.